The effects of poultry slaughter techniques on morphological assessment of apoptosis in skeletal muscles - Shahdan, Intan Azura; Rahman, Mohammad Tariqur (2010)
Methods of slaughter affect the post-mortem biochemical and physiological changes in the conversion of skeletal muscles into meat. apoptosis could be associated with the post-mortem development of meat quality in skeletal muscles of chickens. Apoptosis, a form of cell death, activates the regulation of proteolytic enzymes(caspases) which selectively cleave cytoskeleton proteins and catalyze the changes of cell organelles and morphological structure. These changes are considered to be responsible for meat qualities. In the current study, the influence of methods of slaughter on opoptosis was investigated. Chicken were either decapitate and restrained (D+R+), or neck cutting with intact spinal cord and not restrained (D-R-). The muscles from various parts of chicken were used to observe the morphologic and quantitative changes of opoptosis, during 6 hour storage period. Terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick and-labeling(TUNEL) positive nuclei were detected at time 0, 3 and 6 hour after slaughter. The number of TUNEL-positive nuclei in muscle tissues obtained after either of the slaughter techniques used did not show any significant difference.